Description of a new species of Liropus (Crustacea, Amphipoda) from Puerto Vallarta, Pacific coast of Mexico - Alarcón-Ortega, Lucy C.; Carballo, José L. (Zootaxa, 2022)
A new species of the genus Liropus Mayer, 1920 (Amphipoda, Caprellidae) is described from the Mexican Tropical Pacific coast. Liropus alarconi n. sp. is described on the basis of four specimens collected in association with the tropical marine sponge Trikentrion helium Dickinson, 1945, near to coralline patches, between 23–30 m depth. Liropus alarconi n. sp. can be distinguished from its congeners for the following characters: pereonites 2–5 each with one dorsodistal projection and pereonite 3 with a mediolateral projection.